The suggestive qualities of slogns of banking advertisement (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2016)
meaning are found out, the mechanism of  their influence on consumer is explained. The article deals with the suggestive component of advertising.  The suggestive peculiarities of advertising texts are analysed, the verbal means with suggestive meaning are found out, the mechanism of their influence on a consumer is explained. The article states that it is through advertising that the banking sphere tries to attract attention of consumers. This is why the new ways of suggestion are looked for all the time while trying to persuade the consumers that their bank is the unsurpassed one.The article proves that suggestive meaning is inherent in the words bearing positive information and pointing the social worth of banking services. It is quite often that in the advertising texts we notice adjectives of the highest degree of comparison or the ones that in their semantics perform the meaning of certain “superiority” over the other qualities. They are used to persuade the consumer that what is advertised is the best. Generally, the advertising texts are replete with the attributes helping to call positive associations in a consumer. The review of advertising slogans showed that advertisers often use linguistic units of the national-cultural component, such as geographical names not related to Ukraine, the names of well-known brands and others.Our observations have shown that the characteristics of suggestion of banking advertising slogans is the use of words that are able to convince the consumer in the prestige and the reliability of the bank. These words are also nouns which name social priorities, imperative verbs that are aiming to induce action, personal and possessive pronouns aimed to “bring” banking institution to the consumer, regional vocabulary.
Keywords: suggestion; suggestive qualities; personal pronouns; reflexive pronoun; imperative mood verbs; qualifier; language units with national-cultural component